2014
DOI: 10.1007/s12010-014-1434-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Lactic Acid Bacteria from Traditional Cheese in Khorramabad City of Iran with Probiotic Potential

Abstract: Lactic acid bacteria (LAB) with proteolitic activity are used as aromatic and antibacterial substances, cholesterol reduces, bile salt hydrolyses, and probiotic. The aims of this project were to isolate and identify natural LAB flora involved in traditional fermentation in cheeses of Khoramabad city and also to survey their probiotic potential. In order to achieve this goal, LAB were isolated and characterized using phenotypic and genotypic methods (PCR-sequencing); in the next stage, they were analyzed loweri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…plantarum in coculture may vary during the course of the experiment, as demonstrated by Maldonado-Barragán et al [31]. Induction of antimicrobial peptide synthesis is possible in case of the presence in the environment of the competing organism [14]. It is worth mentioning that high anti- Listeria activity of both studied strains Lb.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…plantarum in coculture may vary during the course of the experiment, as demonstrated by Maldonado-Barragán et al [31]. Induction of antimicrobial peptide synthesis is possible in case of the presence in the environment of the competing organism [14]. It is worth mentioning that high anti- Listeria activity of both studied strains Lb.…”
Section: Resultsmentioning
confidence: 97%
“…En. faecium is a lactic acid bacteria species and is also frequently identified, especially in fresh cheese [14]. …”
Section: Resultsmentioning
confidence: 99%
“…hirae (Azat et al., 2016). Ghahremani, Mardani, and Rezapour (2015) reported that 81% of LAB isolated from traditional cheese in Khorramabad city of Iran belonged to Enterococcus subsp. All these studies demonstrated that the majority of LAB isolated from different traditional cheese from various regions have belonged to Enterococcus genus.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that four strains out of six identified LAB isolates from traditionally fermented Xinjiang cheese were Ent. hirae(Azat et al, 2016) Ghahremani, Mardani, and Rezapour (2015). reported that 81% of LAB isolated from traditional cheese in Khorramabad city of Iran belonged to Enterococcus subsp.…”
mentioning
confidence: 99%
“…Each of these cheeses is characterized by various quality attributes such as a certain race native farming, grazing-based food, as well as knowledge of the master cheese passed down generation after generation, among others. 2 The current demand for fresh and easy to prepare products has brought an increase in the market of minimally processed products. This trend responds to the generalized idea that these foods are healthier.…”
Section: Introductionmentioning
confidence: 99%